Risk-laden migration as a response to relative deprivation: A hypothesis - Oded Stark (University of Bonn, Center for Development Research (ZEF), 2022)
Received migration research has it that higher relative deprivation strengthens the incentive for people to migrate, and that migration is often a risky enterprise. Relative deprivation has been seen as a push factor in migration, and the level of risk involved in migration has been understood to reduce its attraction. Here we show a positive relationship between the level of relative deprivation experienced at origin and willingness to undertake risk-laden migration: we show that higher relative deprivation is matched by riskier acceptable migration options. In expanding the range of acceptable risk-laden migration options, relative deprivation experienced at origin acts also as a pull factor for migration.
Keywords: D81; D91; F22; J61; 330; Social preferences; Relative deprivation; Risk-laden migration